The Effect of Audio Podcast Application on Guessing Meaning Skill on Teaching Listening Comprehension - Aries Fachriza (Educan : Jurnal Pendidikan Islam, 2020)
Audio podcast application is one of media which is appropriate for the learner to train their listening. This quasi experimental research was conducted to investigate the contributions of Audio Podcast Application as a teaching media in listening subject. This research examined whether students achieve better in their understanding on listening passage through skill of guessing meaning of listening by using audio podcast than by using conventional teaching media.The research findings showed the implementation of audio podcast application gives advantages for the learners. The data analysis result showed that the students in experimental group achieved better than the students in control group in their listening comprehension tests. It can be explained that the t value on equal variance assumed were 0.000. Then, the distribution of t table on  = 5%: 2 = 2.5 % (2 -Tailed) with degree of freedom (df) n- 2 (44 -2 = 42) were 2.018  It means  that there was differences between the students who utilized audio podcast application and the students who implemented conventional teaching media in comprehending listening passage by students’ guessing meaning skill, of listening.